Phenomenological Research of Dentist Experiences During the Covid-19 Pandemic - Syafila Nurfathia; CSP Wekadigunawan; Hasyim Hasyim (An-Najat, 2024)
Background The Covid-19 pandemic has resulted in difficulties, including changes in the healthcare service flow, including dental and oral healthcare services, which have become potential sites or mediums for virus transmission. The worsening situation of Covid-19 has compelled dentists to limit procedures in their practice and reduce the number of dental appointments. During the COVID-19 pandemic, mandatory health protocols must be implemented in dental practices, including maintaining physical distancing, limiting direct contact with other individuals, and reducing the number of patient queues in waiting areas. Purpose : Exploring by directly observing dentists regarding their service experiences during the COVID-19 pandemic to provide a concrete, focused, and more vivid description of the experiences felt by dentists based on phenomenological research. Research Methodology : This research employed a qualitative research with a phenomenological approach. The research was conducted for approximately one month at Kaina Healthcare Clinic in West Jakarta. The research sample consists of dentists working at the clinic. Results : Based on the outcomes obtained, 8 themes were identified: dental services continue to operate following health protocols, the most common service is emergency care and tooth abscess treatment, a different workload compared to before the pandemic, mental pressure on dentists, decreased income, ineffective telemedicine, stigma and discrimination, and discomfort when using personal protective equipment (PPE). Conclusion : Based on the theory of organizational behavior, dentists may experience worry and anxiety about the possibility of contracting the virus from patients. However, they must continue to provide service despite the high risk of transmission and reduced income due to decreased patient visits. The information flow or learning effect is that Kaina Healthcare dental clinic continues to operate by following the service procedures during the COVID-19 pandemic. The clinic provides equipment to support COVID-19 prevention efforts. Based on the experience of dentists in providing services during the COVID-19 pandemic, capacity development that has been practiced includes the use of telemedicine. However, this approach has proven to be ineffective because it cannot address the underlying causes of dental problems that require dental treatment. Furthermore, there have been transformational impacts, such as a different workload compared to before the pandemic due to a decrease in patient visits and longer process flows.